Jemaat Philadelphia (Wahyu 3:7-13): Sebuah Tinjauan dari Bahasa Yunani - Chia, Philip Suciadi (Sekolah Tinggi Teologi Injili Indonesia Palu, 2026)
This article examines Jesus Christ’s message to the church in Philadelphia in Revelation 3:7–13 through a Greek-based exegetical approach. The Philadelphian church is one of only two churches in Revelation that receive commendation without rebuke, giving it distinctive theological importance. This study employs Greek syntactical analysis, focusing on the distinction between grammatical form and semantic function, particularly in the use of the genitive case, verbal aspect and tense, and participial and imperative constructions. Historical and archaeological data from the city of Philadelphia in Asia Minor are also considered. The findings indicate that Christ’s title as the holder of the “key of David” underscores His absolute authority to open and shut, granting divine access, protection, and vindication. Despite limited strength and external opposition, the church’s faithfulness becomes the basis for divine praise and eschatological promise. This study demonstrates that careful attention to Greek grammatical features yields important theological insights into the message of Revelation.